Silver nanoparticles induce tight junction disruption and astrocyte neurotoxicity in a rat blood-brain barrier primary triple coculture model - Dan, Mo; Xu, Liming; Shao, Anliang; Cheng, Xiang; Zhang, Cuiping; Yokel, Robert; Takemura, Taro; Hanagata, Nobutaka; Niwa, Masami; Watanabe, Daisuke (International Journal of Nanomedicine, 2015)
Silver nanoparticles (Ag-NPs) can enter the brain and induce neurotoxicity. However, the toxicity of Ag-NPs on the blood-brain barrier (BBB) and the underlying mechanism(s) of action on the BBB and the brain are not well understood. To investigate Ag-NP suspension (Ag-NPS)-induced toxicity, a triple coculture BBB model of rat brain microvascular endothelial cells, pericytes, and astrocytes was established. The BBB permeability and tight junction protein expression in response to Ag-NPS, NP-released Ag ions, and polystyrene-NP exposure were investigated. Ultrastructural changes of the microvascular endothelial cells, pericytes, and astrocytes were observed using transmission electron microscopy (TEM). Global gene expression of astrocytes was measured using a DNA microarray. A triple coculture BBB model of primary rat brain microvascular endothelial cells, pericytes, and astrocytes was established, with the transendothelial electrical resistance values >200 Ω·cm(2). After Ag-NPS exposure for 24 hours, the BBB permeability was significantly increased and expression of the tight junction (TJ) protein ZO-1 was decreased. Discontinuous TJs were also observed between microvascular endothelial cells. After Ag-NPS exposure, severe mitochondrial shrinkage, vacuolations, endoplasmic reticulum expansion, and Ag-NPs were observed in astrocytes by TEM. Global gene expression analysis showed that three genes were upregulated and 20 genes were downregulated in astrocytes treated with Ag-NPS. Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis showed that the 23 genes were associated with metabolic processes, biosynthetic processes, response to stimuli, cell death, the MAPK pathway, and so on. No GO term and KEGG pathways were changed in the released-ion or polystyrene-NP groups. Ag-NPS inhibited the antioxidant defense of the astrocytes by increasing thioredoxin interacting protein, which inhibits the Trx system, and decreasing Nr4a1 and Dusp1. Meanwhile, Ag-NPS induced inflammation and apoptosis through modulation of the MAPK pathway or B-cell lymphoma-2 expression or mTOR activity in astrocytes. These results draw our attention to the importance of Ag-NP-induced toxicity on the neurovascular unit and provide a better understanding of its toxicological mechanisms on astrocytes.